The Design of the Vehicle Tracker tools using Raspberry - Mohammad Hamdani (Institut Sains dan Teknologi Nasional, 2020)
In this paper, it is explained about the design of the Vehicle Tracker tool which is useful in tracking the location of movable assets, by utilizing a GPS receiver USB receiver with a built in antenna, to get coordinates, a Raspberry as a controller and a cellular modem as a media information channel connected to the internet. The controller combines these coordinate information with digital maps obtained from Google Map servers on the internet. When the client accesses the Vehicle Tracker unit via the internet, the controller (Raspberry) provides 'real time' coordinate data along with a digital map. Testing is done by comparing it with GPS Standards with results that are still within the tolerance limit required by GPS International. Latency / delay testing to find out how long the information is sent from the device to the client results in latency / delay under 1 second. Keywords : Vehicle Tracker, GPS, latency, delay, Raspberry